High Circulating Sphingosine 1-Phosphate is a Risk Factor for Osteoporotic Fracture Independent of Fracture Risk Assessment Tool - Lee, Seung Hun; Lee, Jee Yang; Lim, Kyeong-Hye; Lee, Young-Sun; Kim, Seong-Hee; Choi, Sooyoung; Cho, Seong-Hwan; Koh, Jung-Min (Calcified tissue international, 2020)
Circulating sphingosine 1-phosphate (S1P) levels may be a biomarker for osteoporotic fracture (OF). This study assessed whether the addition of S1P levels to the fracture risk assessment tool (FRAX) could improve predictability of OF risk. Plasma S1P concentrations and FRAX variables were measured in 81 subjects with and 341 subjects without OF. S1P levels were higher in subjects with than those without OF (3.11 ± 0.13 μmol/L vs. 2.65 ± 0.61 μmol/L, P = 0.001). Higher S1P levels were associated with a higher likelihood of OF (odds ratio [OR] = 1.33, 95% confidence interval [CI] = 1.05–1.68), even after adjusting for FRAX probabilities. Compared with the lowest S1P tertile, subjects in the middle (OR = 3.37, 95% CI = 1.58–7.22) and highest (OR = 3.65, 95% CI = 1.66–8.03) S1P tertiles had higher rates of OF after adjustment. The addition of S1P levels to FRAX probabilities improved the area under the receiver-operating characteristics curve (AUC) for OF, from 0.708 to 0.769 ( P = 0.013), as well as enhancing category-free net reclassification improvement (NRI = 0.504, 95% CI = 0.271–0.737, P < 0.001) and integrated discrimination improvement (IDI = 0.044, 95% CI = 0.022–0.065, P < 0.001). Adding S1P levels to FRAX probabilities especially in 222 subjects with osteopenia having a FRAX probability of 3.66–20.0% markedly improved the AUC for OF from 0.630 to 0.741 ( P = 0.012), as well as significantly enhancing category-free NRI (0.571, 95% CI = 0.221–0.922, P = 0.001) and IDI (0.060, 95% CI = 0.023–0.097, P = 0.002). S1P is a consistent and significant risk factor of OF independent of FRAX, especially in subjects with osteopenia and low FRAX probability.